2018
DOI: 10.1093/jxb/ery249
|View full text |Cite
|
Sign up to set email alerts
|

FaMYB44.2, a transcriptional repressor, negatively regulates sucrose accumulation in strawberry receptacles through interplay with FaMYB10

Abstract: FaMYB44.2 is a novel transcriptional repressor that modulates both ripening-related and jasmonic acid-related sucrose accumulation in strawberry receptacles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 73 publications
1
60
0
1
Order By: Relevance
“…8f). Beside of the above morphological phenotypes, we also assessed the transcriptional level of downstream genes which indicated fruit ripening, including the softeningrelated genes polygalacturonase (PG), and beta-xylosidase1 (XYL1); the anthocyanin biosynthesis genes dihydroflavonol 4-reductase (DFR) and UDPglucose flavonoid 3-O-glycosyltransferase (UFGT); and the sugar-related genes hexokinase (HXK2) [68][69][70][71]. QRT-PCR analysis showed that the transcript levels of PG, XYL1, DFR, UFGT, and HXK2 were significantly downregulated in the FvPME-RNAi fruits, but upregulated in the overexpressor fruits, compared with the control (Fig.…”
Section: Fvpme38 and Fvpme39 Are Involved In Regulation Of Fruit Softmentioning
confidence: 99%
“…8f). Beside of the above morphological phenotypes, we also assessed the transcriptional level of downstream genes which indicated fruit ripening, including the softeningrelated genes polygalacturonase (PG), and beta-xylosidase1 (XYL1); the anthocyanin biosynthesis genes dihydroflavonol 4-reductase (DFR) and UDPglucose flavonoid 3-O-glycosyltransferase (UFGT); and the sugar-related genes hexokinase (HXK2) [68][69][70][71]. QRT-PCR analysis showed that the transcript levels of PG, XYL1, DFR, UFGT, and HXK2 were significantly downregulated in the FvPME-RNAi fruits, but upregulated in the overexpressor fruits, compared with the control (Fig.…”
Section: Fvpme38 and Fvpme39 Are Involved In Regulation Of Fruit Softmentioning
confidence: 99%
“…The transcription factor AtMYB44 is involved in embryogenesis, seed maturation, responses to pathogens, insects and environmental stresses in Arabidopsis and functions in association with the ethylene signalling pathway (Liu et al ., ). In strawberry, FaMYB44.2 negatively regulates the accumulation of soluble sugar and malic acid content, and may be involved in regulating the production of aroma compounds (Wei et al ., ). MdMYB44 has also been shown to act as a negative regulator in response to cold and salt stress in apple calli (Wu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptional regulation of CHS was achieved by a complex of R2R3-MYB and basic helix-loop-helix (bHLH) transcription factors (TFs) [49]. In strawberry, FaMYB10 regulates FaCHS [40,50]. Considering this regulatory role, we evaluated an effector-reporter system with FaMYB10 as the effector and GUS driven by FaCHS promoter as the reporter to study cellular signal transduction in strawberry fruits.…”
Section: Discussionmentioning
confidence: 99%
“…Besides protoplast-based transient gene expression, transient expression has been increasingly reported in the fruits of many plant species, among which strawberry may be the one that was most extensively studied [6,21,[39][40][41]. We previously conducted a comprehensive study on transient gene expression to optimize and standardize this technique in strawberry fruits [39].…”
Section: Introductionmentioning
confidence: 99%